PENGARUH MODEL PEMBELAJARAN KOOPERATIF TEKNIK BERKIRIM SALAM DAN SOAL TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMP - Nurdiana, Aty; Kirana, Arinta Rara (Epsilon: Jurnal Pendidikan Matematika, 2020)
Abstract: The problems discussed in this study are related to the low mathematics learning outcomes of students in class VIII of SMP Negeri 3 Trimurjo, Central Lampung. Based on this, this study aims to determine whether the cooperative learning model of Sending Greetings and Questions has an effect on the mathematics learning outcomes of eighth grade students of SMP Negeri 3 Trimurjo, Central Lampung. This research is using experimental method. The population in this study was class VIII SMP Negeri 3 Trimurjo Central Lampung which consisted of 3 classes with a total of 94 students and samples from each class amounted to 34 students as samples in the experimental class and 34 students as samples in the control class. Samples were taken using cluster random sampling technique. The instrument in this study used an essay test consisting of 10 items. The results of hypothesis testing using t-test and obtained thit = 9.48 and from the total distribution of t at a significant level of 5% it is known that t(1-Î±) = 2.00. It is proven that thit > tdaf so that it can be concluded that there is an influence of the cooperative learning model of the technique of sending greetings and questions on the Mathematics Learning Outcomes of Class VIII SMP students.